The application of virtual reality technology in gymnastics movement simulation - Feng, M. (Applied Mechanics and Materials, 2012)
The simulation results and the analysis of 3d body movement is still a difficult and hot issue. Although domestic and international counterparts is in a human body movement simulation has some results but they really difficult to meet demand, because height of the complexity of the calculation, or the need to put heavy parameters. Study the hot topic of object-oriented simulation system simulation method, qualitative simulation, distributed interactive simulation, virtual simulation, the multimedia simulation, simulation based on virtual reality.